Effects of ENSO phenomenon on average rainfall dataset - Puangkeaw,N. (2015)
This study aims to investigate an appropriate range of average rainfall in Phuket Province, Thailand for using in GIS applications. Kriging interpolation technique was used in the study. Rainfall data and Historical of ENSO phenomenon between 2002 and 2011 were collected from Meteorology Department, Royal Irrigation Department and NOAA (National Oceanic and Atmospheric Administration), respectively. Three average rainfall data ranges were compared by one-way ANOVA technique including 1) Average rainfall during El Nino period 2) Average rainfall during La Nina period and 3) Average rainfall during Normal period. The results show that the average rainfall was significantly different at 0.05 level. The use of average rainfall in Phuket area should be covered La Nina phenomenon El Nino phenomenon and Normal periods for further related studies.